“Sin of Passion not Principle, nor Even Purpose” - An Exploration of Feminist Consciousness in the Scarlet Letter - Dr. Shumaila Mazhar; Shabana Muhammad Anwar; Qurratul Ain Sardar (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study explores the complexities of the human mind, as revealed through Hester’s character in The Scarlet Letter by Hawthorne. The theoretical framework is based on the theories expounded by Ghazali, the famous 11th-century scholar of the Muslim world, and Freud, the genius of the 20th century. The research design is grounded on a thematic analysis of the selected novel. An exhaustive study of Ghazalain nafs-e-ammara and Freudian id have guided the interpretation of the selected character. The analysis of Hester’s demeanor and ethical principles inside the parameter of the selected theories reveals Hawthorne’s psychological insight. Above and beyond, it also provides a cognizance into the applicability of the psychological issues in the modern world, thus, reinforcing our belief in the corresponding workings of the human mind, irrespective of the variances in time and space. Additionally, it has also revealed that the incorporation of Eastern and Western insights for studying literary character has the potential of becoming an effective critical approach for psychological analysis in the realm of English literature.